PERAN DIGITALISASI TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA INDUSTRI PARIWISATA KECAMATAN TAMBANG KABUPATEN KAMPAR (STUDI KASUS AGRO NADIIN) DI ERA REVOLUSI 4.0 - Kurnia Novri; Iyan Tani Rita; Setiawan Deny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the impact of digitization on the tourism industry in the mining district of Kampar district in the revolutionary era 4.0. The method used in this research is descriptive and quantitative methods. Quantitative descriptive analysis is a study that uses numbers. The population in this study were 118,125 visitors to the Agro Nadiin Sungai Pinang tourism in 2019. Determining the sample in this study used the random sampling technique. So the sample in this study were 100 visitors to Agro Nadin tourism. The data in this study were collected using a questionnaire and analyzed using a descriptive percentage. Based on the research results, it can be seen that digitalization has an impact on the tourism industry in the mining district of Kampar district (Nadiin case study) in the 4.0 revolution era. This is because visitors know Nadiin's tourist attraction from digitization such as social media, Instagram, Facebook and so on. On average, visitors who have come more than 2 times, namely on holidays and weekendsKeywords: Digitalization, Revolution Era 4.0